Psychiatry Core Trainees' Perception of Homophobia in Psychoanalytic Psychotherapy: A Preliminary Survey. (November 2016) - Chatziagorakis, Alexandros; Fitzgerald, Gearoid
Abstract : In 2009 the Royal College of Psychiatrists revised the curriculum for psychiatric training to include psychotherapy elements into the core curriculum. Trainees are now required to provide evidence of treating patients psychotherapeutically. The therapies that the trainees usually deliver are cognitive behavioural therapy and psychoanalytic psychotherapy (PAP). Psychoanalytic theory has largely viewed homosexuality as immaturity or pathology. Psychoanalytic theory and practice have traditionally been unable to incorporate homosexuality as a normal variant of sexuality and this has had significant consequences both for clinical practice and training. Our aim was to examine whether trainees have perceived their experience of PAP as homophobic. The study was done via an internet‐based questionnaire survey. Simple descriptive statistics were used to analyse the results. Most trainees did not find PAP homophobic in theory, practice or supervision. A minority of trainees considered PAP as homophobic prior to undertaking a case and found it homophobic after undertaking a case. Some trainees found their experience of PAP has broadened their views on their sexuality. Participants' experience was positive and PAP was not perceived as homophobic. A negative experience might have significant implications for their mental wellbeing, training and choice of future career.